Empowering Elementary Students Through the Kampus Mengajar Program: Literacy and Numeracy Insights - Apriliatini, Vivi; Elizar (Journal for Lesson and Learning Studies, 2024)
Higher education in Indonesia faces challenges in producing graduates who align with contemporary needs, particularly in enhancing fundamental skills among elementary school students. The Merdeka Belajar Kampus Merdeka (MBKM) initiative seeks to foster flexible and relevant learning. This study aims to analyze the contributions of the fifth cohort of the Kampus Mengajar program in developing students' literacy and numeracy skills. A qualitative approach was employed, utilizing observation and documentation methods for data collection. The subjects were fifth-grade elementary school students, and data analysis was conducted descriptively by categorizing findings based on literacy and numeracy indicators. The results demonstrate that the Kampus Mengajar program positively contributes through activities such as reading corners and a 15-minute literacy program before formal learning sessions. These activities successfully increased students' reading interest, concentration, vocabulary expansion, and critical thinking. Moreover, pre-test results from the Minimum Competency Assessment (AKM) revealed that most students achieved basic literacy competency, providing valuable insights for teachers in designing more focused learning. In conclusion, the Kampus Mengajar program has a significant impact on improving students' literacy and numeracy skills. Recommendations include expanding collaboration with local governments, non-governmental organizations, and donors to provide more adequate resources.